The law and economics of a sustainable energy trade agreement / edited by Gary C. Hufbauer, Ricardo Meléndez-Ortiz and Richard Samans. - Hufbauer, Gary Clyde; Meléndez-Ortiz, Ricardo; Samans, Richard (Cambridge University Press, 2016)
The widely accepted need to reduce the world's dependence on fossil fuels and move instead to low-carbon, renewable alternatives faces a host of challenges. Whilst the greatest challenges remain in engineering, political and public policy issues continue to play a very important role. This volume, which consists of contributions from leading figures in the field, presents the case for a Sustainable Energy Trade Agreement (SETA). It shows that by addressing barriers to trade in goods and services relevant for the supply of clean energy, such an agreement would foster the crucial scaling-up of clean energy supply and promote a shift away from fossil fuels. In doing so it illustrates how the agreement would help to address a number of overarching sustainable development priorities, including the urgent threat of climate change, enhanced energy access and improved energy security. The book will appeal to academics and policymakers working on the interface of trade and energy policy.